Relationship Between Perceived Organizational Support, Proactive Personality, and Perceived Employability in Workers Over 50. Issue 2 (4th June 2018) - Guilbert, Laure; Carrein, Cindy; Guénolé, Nicolas; Monfray, Lise; Rossier, Jérôme; Priolo, Daniel
Abstract : This article examines the relationship between perceived organizational support, proactive personality, and perceived employability in a sample of workers over 50. An online questionnaire assessing these variables were filled by 213 employees. Results confirmed that individual dispositions have a significant impact on perceived employability but also indicated that organizational context may have a greater impact on employability. The implications of the findings are discussed, and suggestions are offered for future research on employability.